If it's not what You are looking for type in the equation solver your own equation and let us solve it.
28*y^6-(((8*y^3)/4)*y^3) = 0
{root[2][25]}
3;14
-5/2 = -5
1;9;0;0;0;22
| 28y^6-8y^3/4y^3 | | 3x+2-6=4 | | 2+8+-43+[-12]=20 | | |3x-3/9|1 | | 9xy-4x+y= | | 24x+5=42 | | 4y+8=4y+4 | | 3x-3/91 | | 3y-9=x+1 | | 8x^2-28x-23=0 | | 9xy-4xy+y= | | H+20= | | y^2-at+7by-7ab=0 | | -1=-1/5x | | 3x-2(x+6)=-24 | | 11q-145=13 | | 4(v-4)=6v-22 | | (-7)-0= | | 0.09xX=43.43 | | 3+7=-11+2x | | -3+5(8+6)=37 | | 5bx^2-7ax=0 | | 3cosx-2=7 | | 6(m-2)+14=3(m+2)-6 | | -369+3x=12x+153 | | 2(x+7)=28-18-3(6-x) | | 0.09xX=57.51 | | x/.4-2x | | 21a-12=72 | | 2x+224=11x-10 | | 2ax-x-2ax= | | -215=5x+5(-3x-23) |